Development of practical drag model for multirotor-type unmanned aerial vehicles and its application - Lim, D.; Kim, H.; Yee, K. (My University, 2019)
Application area of multirotor-type Unmanned Aerial Vehicles have become popular and diverse in recent years. This trend makes it more important to obtain an optimally designed multirotor for a specific mission in the conceptual design phase. To this end, accurate prediction of a forward flight performance is essential, and one of the most influential factors on forward flight performance is drag force induced by the body frame. In this study, a practical drag estimation model for multirotor-type Unmanned Aerial Vehicles is developed for the conceptual design phase. The drag model is developed based on physical geometry of the body frame of the multirotors considering interference effect between the components. Therefore, the developed model is able to estimate a drag force depending on the variation of the multirotor geometry. The model estimates the drag force through regression equations derived from Computational Fluid Dynamics (CFD) analysis, which makes the model fast and accurate. The drag model is eventually embedded in a design optimization framework. For a generic filming mission, an optimization example is presented with comparative analysis depending on whether the drag model is applied or not. The optimization result shows that the significance of the drag coefficient on the design optimization